2020
DOI: 10.14712/fb2020066030104
|View full text |Cite
|
Sign up to set email alerts
|

Protumorogenic Potential of Pancreatic Adenocarcinoma-Derived Extracellular Vesicles

Monika Baj-Krzyworzeka,
B. Mytar,
K. Węglarczyk
et al.

Abstract: Cancer development is a highly complicated process in which tumour growth depends on the development of its vascularization system. To support their own growth, tumour cells significantly modify their microenvironment. One of such modifications inflicted by tumours is stimulation of endothelial cell migration and proliferation. There is accumulating evidence that extracellular vesicles (EVs) secreted by tumour cells (tumour-derived EVs, TEVs) may be regarded as “messengers” with the potential for affecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Last but not least, Baj-Krzyworzeka M et al demonstrated the pro-angiogenic activity of EVs originated from human PDAC cell lines (HPC-4) in vitro, as well as in immunodeficient mice in vivo [ 156 ]. It was also observed that these EVs induced increased proliferation and migratory behavior of human umbilical vein endothelial cells (HUVEC), as well as induced cytokine production, such as VEGF and IL-8, which constitute pro-angiogenic factors that facilitate neovascularization [ 156 ].…”
Section: The Effects Of Evs In Pdac-associated Thrombosismentioning
confidence: 99%
“…Last but not least, Baj-Krzyworzeka M et al demonstrated the pro-angiogenic activity of EVs originated from human PDAC cell lines (HPC-4) in vitro, as well as in immunodeficient mice in vivo [ 156 ]. It was also observed that these EVs induced increased proliferation and migratory behavior of human umbilical vein endothelial cells (HUVEC), as well as induced cytokine production, such as VEGF and IL-8, which constitute pro-angiogenic factors that facilitate neovascularization [ 156 ].…”
Section: The Effects Of Evs In Pdac-associated Thrombosismentioning
confidence: 99%